The impact of membrane composition on conformation and trafficking of lipidated prion protein (PrP) variants - Hackl, Stefanie (Nanyang Technological University, 2020)
Prion protein (PrP) aggregation arises from the misfolding of the native cellular PrP (PrPC) and is a key pathophysiologic event in fatal neurodegenerative prion diseases. To elucidate the mechanism of conversion of PrPC into toxic PrPSc, homogeneous PrP constructs carrying a glycosylphosphatidylinositol (GPI) anchor mimic served as tools to directly observe PrP at the cellular membrane, the initial site of prion infection and PrP misfolding. The posttranslational modifications (PTMs) of PrP, especially the GPI anchor, have been shown to be crucially involved in PrPSc formation. To this end, fluorescently labeled, folded PrP variants equipped with GPI anchor-mimicking peptides were generated via a semisynthesis approach. Secondary structures of the resulting PrP constructs were assessed by circular dichroism (CD). All PrP variants exhibited typical far-UV CD spectra of predominantly α-helical proteins, in agreement with the structure of native PrPC. In vitro aggregation, monitored by thioflavin T (ThT) fluorescence and proteinase K (PK) resistance, illustrated their use in understanding key steps of PrP pathology.To study the PrP-membrane interaction, we monitored PrP association on artificial supported bilayers in quartz crystal microbalance-dissipation (QCM-D) experiments in real time, varying pH, lipid and salt compositions. Upon increasing the PrP concentration in close proximity of the bilayer by enhancing the initial electrostatic interaction, lipidated PrP variants, in particular the full-length PrP construct (aa 23-231), exhibited a higher binding affinity towards the bilayer compared to recombinant PrP. This finding corroborates the significance of the GPI anchor mimic in PrP-membrane interactions.Further cell imaging experiments using super-resolution structured illumination microscopy (SR-SIM) combined with co-localization analysis confirmed the membrane localization of Cy5 labeled PrP constructs equipped with a GPI anchor mimic in neuron-like SH-SY5Y cells. The dynamic behavior of PrP within the ordered and disordered regions of the plasma membrane as well as the actin cytoskeleton was studied extensively with fluorescence correlation spectroscopy (FCS). Imaging total internal reflection-FCS (ITIR-FCS) measurements demonstrated that full-length PrP modified with a GPI anchor mimic affected the cholesterol-dependent membrane domains by making them more fluid. No such impact was observed for PrP without a GPI anchor mimic. This emphasizes the significance of the interaction between the cellular membrane, PrP and its GPI anchor in cells. By combining methyl-β-cyclodextrin (mβCD) treatments, a cholesterol-depleting agent, with addition of latrunculin A (LatA), an actin polymerization inhibitor, the interaction of lipidated PrP labeled with Cy5 in its membrane environment was studied. FCS revealed that PrP containing a GPI anchor mimic exhibits a lower (compared to free diffusing species), cholesterol-independent and cytoskeleton-dependent mobility. Manipulation of the link between PrP and the cytoskeleton by inhibiting actin polymerization induced an even slower diffusion of Cy5 labeled PrP. Typically, decelaration of diffusion is attributed to protein clustering, which could resemble the initial step of PrP aggregation. We propose that an intact actin cytoskeleton can act as a barrier for the conversion of PrPC into PrPSc on cell membranes. Thus, the cytoskeleton-membrane association that immobilizes PrP via the actin cytoskeleton can be hypothesized to play a crucial role in the PrPC-PrPSc conversion. By taking advantage of site-selectively modified PrP variants and biophysical investigations of their interactions with membranes, including a complex live cell setting, we gained an improved understanding of the synergistic interplay between PrP, its GPI anchor, the cellular membrane and the cytoskeleton.